Next viewer–development of a software for the spatial computing data glasses apple vision pro for patient-specific preoperative planning and navigation - Conrad Günther; Dirk Winkler; Svenja Jung; Martin Hoffmann; Katharina Scheidt; Fabian Kropla; Erdem Güresir; Ronny Grunert (Frontiers in Digital Health, 2026)
Objective This study aims to evaluate the clinical utility of nextViewer , a novel spatial computing application for the Apple Vision Pro, to determine its efficacy in enhancing patient-specific neurosurgical preoperative planning, spatial comprehension, and multi-user team communication. Methods A complete translational workflow was established, encompassing the segmentation of high-resolution CT/MRI scans into patient-specific 3D models and their integration into the spatial computing environment. The software leverages integrated eye- and hand-tracking to enable controller-free interaction, including 3D model manipulation, surgical trajectory drawing, and multiplanar finger-navigation. A systematic clinical evaluation was conducted with 15 experienced neurosurgeons. User satisfaction regarding user-friendliness, surgical planning benefits, system stability, and visualization quality was assessed utilizing a Likert-scale questionnaire ranging from −2 (strongly disagree) to +2 (strongly agree). Results The application successfully facilitated intuitive, real-time manipulation of complex anatomical models, utilizing transparencies to visualize underlying critical structures. The finger-navigation feature—providing immediate crosshair updates in corresponding coronal, sagittal, and axial planes—was identified as a unique selling point for spatial orientation. Furthermore, the collaboration mode enabled synchronized, multi-user case discussions. The systematic evaluation yielded a highly positive total score of +1.7. Surgeons specifically highlighted the controller-free interaction and the exceptional graphical resolution as significant advantages over legacy visualization systems. Conclusions Controller-free spatial computing via the Apple Vision Pro significantly enhances neurosurgical preoperative planning. By improving real-time spatial awareness and enabling seamless interactive simulations, the nextViewer app bridges the gap between theoretical augmented reality concepts and practical clinical application. The system demonstrates strong potential to become a standard tool in neurosurgery, establishing a robust foundation for future integration with telemedicine and advanced surgical navigation.